STRATEGI PENGEMBANGAN PEMBELAJARAN PAI DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI SMPN 1 PERAK - Mahfudoh, Iftani Lailatul; Sirojudin, Didin (JoEMS (Journal of Education and Management Studies), 2021)
This study aims to describe the strategy of developing Islamic religious education learning in improving student achievement at SMPN 1 Perak. The strategy of developing Islamic religious education learning can be identified by analyzing primary data and secondary data at SMPN 1 Perak. This study uses a qualitative design. The data analyzed is data from the main sources of this study, namely the principal, student council, curriculum waka, Islamic religious education subject teachers and students. In addition, data sources can also be obtained by observing and other documents related to research. The results of the study were analyzed using three stages, namely data reduction, data presentation and conclusion drawing. The results of the study stated that the strategy of developing Islamic religious education learning in improving student achievement at SMPN 1 Perak was carried out in the classroom and outside the classroom.